Influence Of Satisfaction Level Patient To Outpatien Services In Hospitals (Case Study In Private Hospitals In West Jakarta) - Irisha Kirana Wiradisuria; Agustinus Purna Irawan (UNIVERSITAS PAKUAN, 2025)
The background of this study is to understand how the level of patient satisfaction can affect the image and performance of a hospital, and to identify factors that contribute to patients' satisfaction and/or dissatisfaction. This study also aims to provide strategic recommendations for hospitals in improving the quality of service and creating a better patient experience. This study aims to identify and analyze factors that influence patient satisfaction in hospitals, focusing on the quality of medical services, hospital facilities, communication between patients and health workers, and service waiting time. Through a quantitative approach using a survey of 200 respondents consisting of outpatients and inpatients, the data obtained were analyzed using appropriate statistical methods, such as linear regression or SEM-PLS analysis, to identify the relationship between the variables studied. The results of the analysis were used to draw conclusions about the factors that most influence patient satisfaction. The final step is the preparation of a research report containing the main findings and recommendations for hospitals in improving the quality of service and overall patient satisfaction. The results of the study indicate that the quality of medical services and communication between patients and health workers have a significant influence on the level of patient satisfaction. In addition, hospital facilities and service waiting time also contribute to determining patient satisfaction, although to a lesser extent. SW Hospital needs to maintain and continuously improve the quality of medical services and existing facilities to ensure patient satisfaction levels remain high.